Technological innovations and social development in Asia. Issue 1 (2nd January 2019) - Li, Bingqin; Piachaud, David
ABSTRACT: It is increasingly a concern that technological innovations may create as many problems as they solve. Together with the articles in this special issue, we outline the challenges and opportunities posed by technological changes to social development and the mechanisms through which technological innovations may deliver or prevent social development. The experience in Asia in this collection shows the attempt to use technological innovations to overcome hurdles for social development in multiple spheres, by the state, the market and the society. Despite of the anticipation for technology innovations to work wonder, the outcomes are far from being certain.